Layanan di Perpustakaan Jurusan Bahasa dan Sastra Indonesia dan Daerah - Monika Pratiwi; Bakhtaruddin Nst. (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this paper were to describe the quality of library services and the level of student satisfaction in the Department of Language and Literature of Indonesia and the Region. Data were collected through LibQUAL+TM questionnaires. Based on the results of the data analysis, it was found that the quality of library services of Indonesian Language and Literature and the Regions Department has not been able to meet the expectations of the users. The variables (overall dimensions) showed that users’ minimum expectations was not be able to meet users’ expectation. Only two variables, namely the influence of the service, and the ease of obtaining information were fulfilled, whereas the variable library building, and access to information and the collection has not met users’ minimum expectations. Overall, the respondents do not feel satisfied with the services received. Keywords: library services; user satisfaction; LibQUAL+TM